Study of the causes and factors which affect compliance of the patient in directly observed short course chemotherapy in pulmonary tuberculosis in Central India - Saxena, Vivek; Saxena, Shreshtha (International Journal of Research in Medical Sciences, 2017)
Background: TB is one of the most ancient diseases. World Health Organization (WHO) estimated 9.2 million new cases in 2014 out of which 2.2 million were from India. National tuberculosis programme was started since 1962 and short course chemotherapy was included in 1983. With this background in 1992 WHO and Swedish International Development Agency (SIDA) reviewed the programme. As a result, revised national tuberculosis programme (RNTCP) was started. RNTCP recommended directly observed short course chemotherapy in pulmonary tuberculosis (DOTS) and was implemented in 1993. Objective of present study was to find out the causes and factors affecting compliance of the patients in directly observed short course chemotherapy in pulmonary tuberculosis. Methods: We studied 100 patients of pulmonary tuberculosis, who were sputum smear positive for tubercle bacilli. Patients were treated with DOTS (Directly Observed Short Course Chemotherapy) recommended by RNTCP and we observed the causes and factors responsible for interruption of the treatment in noncompliant patients. Results: Overall compliance was 78% and 22% patients were noncompliant. Most common cause of noncompliance was side effects of drugs (12%), noncompliance was maximum (45.45%) between age group of 15-25 years. Illiterate and low socioeconomic status patients were more noncompliant 46.45% and 63.63% respectively. Conclusions: Eventually, after seeing all merits and demerits of DOTS, we have concluded that intensive health education may have favourable impact to improve further outcome of DOTS and compliance of the patients.